The impact of aerobic and balance exercises on anxiety and dizziness in post-COVID-19 patients: a randomised clinical trial - Mabrouk, Mohamed Ibrahim; Abdalbary, Sahar Ahmed; Abdelmonem, Asmaa Foad; Abdelhakiem, Nadia Mohamed; Ahmed, Alaa Anwar; Gelany, Fatheia Mostafa; El Rahim, Ahmed A. Abd (Physiotherapy quarterly, 2025)
Introduction Examine how aerobic exercises, relaxation techniques, and balance exercises affect patients’ anxiety and dizziness post-COVID-19 patients. Methods Thirty participants post-COVID-19, complaining of anxiety and dizziness, aged 45–65 years, of both sexes, selected from the outpatient clinic of our hospital, were enrolled in the study after a COVID-19 infection. Treatment sessions were 3 times weekly for 4 weeks, and the patients were treated separately in group therapy. The 15 patients in group A were given aerobic, balancing, and relaxation techniques. The 15 patients in the control group (group B) were given only relaxation exercises. Assessments of the two groups were completed both before and after the course of treatment by the Hamilton Anxiety Scale (HAMA) and the Berg Balance Scale. Respiratory function was also assessed using maximum voluntary ventilation. Results There were significant differences between the two groups after the treatment. The mean values of the HAMA after treatment were 17.2 ± 1.7 and 21.7 ± 1.4 in groups A and B, respectively. After treatment, the mean values of the Berg Balance Scale were 26.7 ± 5.7 and 22.2 ± 3.6 in groups A and B, respectively. The mean values of maximum voluntary ventilation were 117.2 ± 16.7 and 108.1 ± 16.3 in groups A and B, respectively. Both groups showed a significant decrease in anxiety and dizziness and a significant increase in maximum voluntary ventilation at the end of the 4 weeks of the training program. Participants in group A showed a significantly greater decrease in anxiety and dizziness and a significantly greater increase in maximum voluntary ventilation ( p < 0.05) after the training program. Conclusions Ultimately, it can be said that aerobic exercises, balance exercises, and relaxation techniques can raise maximal voluntary breathing and lessen anxiety and dizziness in post-COVID patients. Therefore, it might be regarded as a successful, secure, cost-effective, and efficient supplementary treatment method for lowering anxiety and vertigo in COVID-19 patients.